Effect of TMP-based-cottonseed oil-biolubricant blends on tribological behavior of cylinder liner-piston ring combinations - Gul, M.; Mohd Zulkifli, Nurin Wahidah; Masjuki, Haji Hassan; Abul Kalam, Mohammad; Mujtaba, M. A.; Harith, M. H.; Syahir, A. Z.; Ahmed, Waqar; Farooq, Abdul Bari (Elsevier Ltd., 2020)
Cottonseed oil-based biolubricant was synthesized by the TMP-based transesterification process. 10–50% by volume blends of TMP-based cotton-biolubricant and SAE-40 were prepared and tested on the high-frequency-reciprocating-rig with engine cylinder-liner and piston-ring combination to investigate their tribology. While tribological characteristics were also evaluated by four-ball tribo-testers at high constant load of 785 N. 10% addition of cotton-biolubricant showed the lowest friction and wear as compared to SAE-40 but>10% volume of cotton biolubricant in blend increased the wear and friction considerably as tested by both HFRR and four-ball. Hence, 10% addition of TMP-cotton-biolubricant can be utilized as an energy-saving lubricant additive to partially reduce the dependency on petroleum-based lubricant for automotive engine application.